Cryoglobulinemic Glomerulonephritis Presenting as Acute Kidney Injury on Chronic Kidney Disease in Rheumatoid Arthritis - Brinda Basida; Nirav Zalavadiya; Mahesha Makandura; Malitha Hettiarachchi (Annals of Internal Medicine: Clinical Cases)
Cryoglobulinemic vasculitis (CV) is one of the manifestations of rheumatoid arthritis (RA). Here, we present a case of a 69-year-old woman with uncontrolled long-standing RA who presented with heart failure exacerbation and had an incidental finding of persistent acute kidney injury, which led to the diagnosis of CV. The rarity of its co-occurrence with RA and the serious consequences from progressive kidney damage makes this case a key learning encounter.